1976
DOI: 10.3758/bf03214029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habituation on threat display and dominance establishment in the Siamese fighting fish,Betta splendens

Abstract: In three separate experiments, male Betta splendens were exposed, respectively, to mirror images, a variety of conspecifics, and to future opponents, prior to combat with unexposed sUbjects. Threat display to mirror images and to live opponents habituated significantly, but the outcomes of dominancesubordinance tests were not significantly affected by prior exposure to any of the threat-eliciting stimuli. Results are discussed in terms of stimulus and response specificity and possible chemical suppression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…The responsiveness then wanes until after 5 min exposure to the mirror; the duration of gill-cover erection is less than when there is no mirror exposure at all. This waning in responsiveness is in agreement with earlier reports of habituation of aggression in this species (Baenninger, 1966;Clayton & Hinde, 1968;Figler, 1972;Meliska & Meliska, 1976;Peeke & Peeke, 1970), although for most of these earlier studies much longer periods of exposure were needed to demonstrate habituation. The much shorter exposures needed for the reduction of responsiveness in the present experiment might 300 -.. odel).…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…The responsiveness then wanes until after 5 min exposure to the mirror; the duration of gill-cover erection is less than when there is no mirror exposure at all. This waning in responsiveness is in agreement with earlier reports of habituation of aggression in this species (Baenninger, 1966;Clayton & Hinde, 1968;Figler, 1972;Meliska & Meliska, 1976;Peeke & Peeke, 1970), although for most of these earlier studies much longer periods of exposure were needed to demonstrate habituation. The much shorter exposures needed for the reduction of responsiveness in the present experiment might 300 -.. odel).…”
Section: Methodssupporting
confidence: 81%
“…Most of these studies have used prolonged exposure to a live conspecific or to a mirror image to induce habituation. However, waning of responsiveness is also obtained when relatively short periods of exposure are given at 24 h intervals (e.g., Figler, 1972;Meliska & Meliska, 1976;Peeke & Peeke, 1970).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and intensity of these displays, which are characterized by gill-cover extension and fin erection, wane after prolonged exposure to such stimuli. The decrease in aggressive behavior observed following such visual exposure, however, does not generalize to situations involving physical combat (Lobb & McCain, 1976;Meliska & Meliska, 1976). The decrease in displaying may be stimulus specific (Baenninger & Mattleman, 1973;Klein, Figler, & Peeke, 1976), or it may reflect the lack of aversive consequences inherent in the manner of stimulation (Lobb & McCain, 1976).…”
mentioning
confidence: 99%
“…The vigor with which animals present their display, defined by the duration and frequency of the demonstration, is a reliable predictor of the animal's performance in a real combat situation (Evans, 1985) and in situations in which dominance is established (Baenninger, 1968;Meliska & Meliska, 1976;Meliska et al, 1975Meliska et al, , 1980Simpson, 1968). Rhoad, Kalat, and Lopfer (1975) showed that the agonistic display in Bettas is more vigorous when they are presented with a male of the same species, followed by a mirror image, a moving model, and finally, a stationary model.…”
mentioning
confidence: 99%